Use of behavioural latencies to assess the value of sand floor in blue fox (Vulpes Lagopus) - Orjala, Hanna; Koistinen, Tarja; Korhonen, Hannu T. (Finnish Society for Applied Ethology, 2010)
Farmed blue foxes utilise a sand floor when it is available. They perform various activities on the sand, e.g. exploration, sniffing, digging and object play. It is unclear, which of the possible activities the foxes use the sand floor for. Our aim was to study why blue foxes enter the sand floor from a mesh floor and vice versa by using the order and latencies of various behaviours after entrance. Each experimental cage (n = 8) consisted of two cages, one with a mesh floor and one with a sand floor. The cages were connected with two one-way doors, to which weights could be added. The orders of the occurrence of various behaviours were video recorded and their latencies were measured after entrance to a cage with 0 and 2.5 kg of extra weight on the door in 15 juvenile blue foxes. The results were analysed with a linear mixed model analysis. After entering the mesh floor, the foxes most commonly first observed surroundings outside the cage (in 44% of 131 analysed entries), explored the cage (32%) and contacted the neighbouring fox (12%). Observing (39%) and exploration (32%) were common also as second behaviours. Other common second behaviours were resting (11%) and eating (6%). After entering the sand floor, the foxes first observed surroundings (in 37% of 129 analysed entries), sniffed (33%) and contacted the neighbouring fox (13%). The most common second behaviours were inspection of the cage (30%), sniffing (29%) and contact with the neighbouring fox (18%). In general, more elimination and food hiding, and less resting and contact with neighbouring fox was observed on sand than on mesh. The latency of sniffing sand (19±3 sec, mean± SE) was shorter than that of digging (97±9 sec).The latencies to play with a neighbour (Sand: 72±19 sec; Mesh: 36±16 sec, F1, 31=7.4, P<0.01) and inspect the cage (Sand: 53 ± 8 sec; Mesh: 23 ± 4 sec, F1, 153=29.3, P<0.001) were significantly longer on sand than on mesh. The latency of solitary play tended to be longer on sand than on mesh (Sand: 112 ± 16 sec; Mesh: 65 ± 25 ...